Development of a double-frequency elliptical vibration cutting apparatus for freeform surface diamond machining. Issue 5 (November 2016) - Zhou, Xiaoqin; Zuo, Chengming; Liu, Qiang; Wang, Rongqi; Lin, Jieqiong
Abstract A new apparatus is proposed for the freeform surface diamond machining on die steel in this paper. Fast tool servo-based diamond turning is considered to be the most effective and efficient generating technology for freeform surfaces, but freeform surfaces of die steel cannot be machined very effectively by this technology because of the severe tool wear and the surface quality degradation. Elliptical vibration cutting has demonstrated excellent performances in machining die steel materials. Therefore, this paper proposes a double-frequency elliptical vibration cutting apparatus, which combines fast tool servo and elliptical vibration cutting. The device is designed to be a flexure hinge structure and driven by two piezoelectric actuators to generate tool motions. A series of testing experiments are conducted, in which the device performs well. In addition, the freeform surfaces are generated on the 40Cr die steel workpieces with the device, and the surface machined by double-frequency elliptical vibration cutting shows much better surface integrity and form accuracy than the surface machined by conventional fast tool servo, which validates the principle and the proposed apparatus.